2020
DOI: 10.17691/stm2020.12.6.09
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor Technologies in Medicine: from Detection of Biochemical Markers to Research into Molecular Targets (Review)

Abstract: Infections are a major cause of premature death. Fast and accurate laboratory diagnostics of infectious diseases is a key condition for the timely initiation and success of treatment. Potentially, it can reduce morbidity, as well as prevent the outbreak and spread of dangerous epidemics. The traditional methods of laboratory diagnostics of infectious diseases are quite time- and labour-consuming, require expensive equipment and trained personnel, which is crucial within limited resources. The fast biosensor-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…Sheng et al ( 116 ) developed a label-free biosensor with an RNA aptamer for the sensitive, rapid quantitative detection of food pathogens without the isolation, purification and enrichment processes. A further study found that optical label-free biosensors can detect and quantify MTB, mycobacterial proteins and interferons quickly and efficiently, making them beneficial for the early detection of tuberculosis ( 117 ). Fluorescence in situ hybridization (FISH) is a molecular diagnostic technique used to detect and localize specific nucleic acid sequences in cells.…”
Section: Other Molecular Diagnostic Techniquesmentioning
confidence: 99%
“…Sheng et al ( 116 ) developed a label-free biosensor with an RNA aptamer for the sensitive, rapid quantitative detection of food pathogens without the isolation, purification and enrichment processes. A further study found that optical label-free biosensors can detect and quantify MTB, mycobacterial proteins and interferons quickly and efficiently, making them beneficial for the early detection of tuberculosis ( 117 ). Fluorescence in situ hybridization (FISH) is a molecular diagnostic technique used to detect and localize specific nucleic acid sequences in cells.…”
Section: Other Molecular Diagnostic Techniquesmentioning
confidence: 99%
“…Humankind experiences a death toll of around 2 million lives yearly from increasing bacterial resistance to antibiotics and viral infections [9]. An increasing need to develop new diagnostic tools for better detection of pathogens was revealed during the COVID-19 pandemic.…”
Section: Biosensors With Bio-coatings and Applications In The Health ...mentioning
confidence: 99%
“…Briefly, biosensors are devices used to analyse the concentration of a specific target component with the help of a sensitive biological element. They can detect, record, and transmit selective, quantitative, or semi-quantitative analytical information about biochemical reactions [9]. A biosensor includes a substrate, typically paper, glass, or silicon.…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors are small integrated analytical devices consisting of biological components in close contact with physical sensors that convert the biometric process to measurable signals. They provide specific quantitative or semi-quantitative analytical information using biometric elements that convert information from the biological domain into chemical or physical output signals 77 , 78 , 79 .…”
Section: Application Of Biotechnology In Pharmaceutical Manufacturing...mentioning
confidence: 99%